Remediation of Lead-contaminated Farmland Soil: Efficacy of Low-cost Natural Amendments in [Im]mobilization of Lead - Himawan, Himawan; Rahardjo, Sentot Budi; Suntoro, Suntoro; Setyono, Prabang (AGRIVITA, Journal of Agricultural Science, 2021)
The control of Pb mobility is a success key in remediation of contaminated soil. This research aimed to explore the effective low-cost amendments in mobilizing or immobilizing lead in contaminated soil, assess environmental risk, and evaluate important amendment properties. Lead-contaminated soil was incubated with 13 materials included chars, bioslurry, limes, rice husk, gypsum, citric acid, natural organic acids and the efficiency of lead immobilization (E) was studied. Soil incubated with 10% amendments was sequentially extracted to determine Pb geochemical fractions and its risk. Selected amendment properties were evaluated through a correlation study with E. The results showed that 6 amendments immobilized lead in the order of chars > gypsum > bioslurry > rice husk. Chicken manure and chicken bone biochars, effectively decreasing lead solubility, were the best immobilising amendments, redistributed lead into the residual fraction and remediated the soil from moderate to low environmental risk. The order of mobilizing amendments was: citric acid > baby orange juice > limes > tamarind > lemon juice > tomato. The citric acid was the most effective mobilizing amendment which increased soluble lead and shifted the soil into high environmental risk status. The three most important amendment properties in influencing soil-Pb mobility were pH, P, and Ca content.